Uptake of leptin and albumin via separate pathways in proximal tubule cells. (October 2016) - Briffa, Jessica F.; Grinfeld, Esther; Poronnik, Philip; McAinch, Andrew J.; Hryciw, Deanne H.
Graphical abstract: Abstract: The adipokine leptin and oncotic protein albumin are endocytosed in the proximal tubule via the scavenger receptor megalin. Leptin reduces megalin expression and activates cell signalling pathways that upregulate fibrotic protein expression. The aim of this study was to investigate if leptin uptake in proximal tubule cells was via the albumin-megalin endocytic complex. In immortalised proximal tubule Opossum kidney cells (OK) fluorescent leptin and albumin co-localised following 5 min exposure, however there was no co-localisation at 10, 20 and 30 min exposure. In OK cells, acute exposure to leptin for 2 h did not alter NHE3, ClC-5, NHERF1 and NHERF2 mRNA. However, acute leptin exposure increased NHERF2 protein expression in proximal tubule cells. In OK cells, immunoprecipitation experimentation indicated leptin did not bind to ClC-5. Leptin uptake in OK cells was enhanced by bafilomycin and ammonium chloride treatment, demonstrating that uptake was not dependent on lysosomal pH. Thus, it is likely that two pools of megalin exist in proximal tubule cells to facilitate separate uptake of leptin and albumin by endocytosis.